Lecanemab for mild Alzheimer disease – is there a way forward? - Rajesh R Tampi (Drugs in Context)
This Editorial reviews data on the efficacy and adverse effects of lecanemab amongst individuals with mild Alzheimer disease. Additionally, the recent controversy regarding the rejection by the EMA of a marketing authorization request for lecanemab, followed by its subsequent approval, is also discussed. The need for thoughtful discussions regarding the risks and benefits of this medication as well as the importance of developing Appropriate Use Recommendations and/or national guidelines for the use of lecanemab are also highlighted.